2021
DOI: 10.1038/s41419-021-03747-z
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with hyaluronic acid metabolism suppresses glioma cell proliferation by regulating autophagy

Abstract: The tumor microenvironment plays an important role in tumor progression. Hyaluronic acid (HA), an important component of the extracellular matrix in the tumor microenvironment, abnormally accumulates in a variety of tumors. However, the role of abnormal HA accumulation in glioma remains unclear. The present study indicated that HA, hyaluronic acid synthase 3 (HAS3), and a receptor of HA named CD44 were expressed at high levels in human glioma tissues and negatively correlated with the prognosis of patients wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…Clinically, 4MU is often used to relieve biliary spasm [ 25 ]. Moreover, we confirmed that 4MU as HA inhibitor could suppress glioma growth in previous research [ 20 ]. Meanwhile, CD47 expression in hepatic cancer stem cells can be inhibited by 4MU [ 26 ], and CD47-SIRPα axis exerts an inhibitory effect on the ability of macrophages to phagocytose cancer cells [ 27 ].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Clinically, 4MU is often used to relieve biliary spasm [ 25 ]. Moreover, we confirmed that 4MU as HA inhibitor could suppress glioma growth in previous research [ 20 ]. Meanwhile, CD47 expression in hepatic cancer stem cells can be inhibited by 4MU [ 26 ], and CD47-SIRPα axis exerts an inhibitory effect on the ability of macrophages to phagocytose cancer cells [ 27 ].…”
Section: Resultssupporting
confidence: 88%
“…In previous study, we confirmed that glioblastoma growth could be inhibited by 4MU treatment or HAS3 silencing via inhibiting HA synthesis [ 20 ]. To confirm whether the HA abnormal accumulation in glioblastoma could regulate macrophages polarization, U251 and LN229 cell lines were subjected to 4MU treatment or HAS3 silencing in vitro for 48 h. Then, the culture supernatant was collected and mixed with RPMI-1640 to obtain different conditioned medium (CM).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…These authors demonstrated that, in the GL26 murine GBM cell line, 4-MU diminished HA synthesis while increasing apoptosis and decreasing cell proliferation and migration (66). Yan et al found that alterations in HA metabolism, by silencing HAS3 or by treating with 4-MU, inhibited glioma cell proliferation by affecting the autophagy flux (67). Although these new results are encouraging, more investigations are needed to understand the action and mechanism of 4-MU in GBM cells.…”
Section: Glioblastomamentioning
confidence: 99%